2013
DOI: 10.2169/internalmedicine.52.0339
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Need to Initiate Noninvasive Ventilation in Stable Outpatients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Objective Predictors of the need to initiate noninvasive ventilation (NIV) in stable COPD outpatients with acute exacerbation of chronic obstructive pulmonary disease (COPD-AE) are insufficiently defined. The objective of this study was to investigate predictors of the need to initiate NIV in stable COPD-AE outpatients. Methods A total of 140 consecutive stable COPD outpatients who were hospitalized for COPD-AE for the first time were retrospectively examined. Demographic and clinical parameters measured in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…Importantly, the present study extended these findings to patients who suffered from COPD and concurrent OSA, and demonstrated that CT90% and PCO 2 while awake predict CPAP failure in the OSA-COPD overlap syndrome. Interestingly, neither the severity of OSA nor the degree of airflow limitation independently predicted CPAP failure in the present study, which was in agreement with previous reports [23]. At present, it remains unknown whether initial PAP titration success relates to long-term favourable outcomes of PAP therapy in patients with OSA and concurrent COPD, and further studies are necessary to analyze such relationships.…”
Section: Comment [Jm14]supporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, the present study extended these findings to patients who suffered from COPD and concurrent OSA, and demonstrated that CT90% and PCO 2 while awake predict CPAP failure in the OSA-COPD overlap syndrome. Interestingly, neither the severity of OSA nor the degree of airflow limitation independently predicted CPAP failure in the present study, which was in agreement with previous reports [23]. At present, it remains unknown whether initial PAP titration success relates to long-term favourable outcomes of PAP therapy in patients with OSA and concurrent COPD, and further studies are necessary to analyze such relationships.…”
Section: Comment [Jm14]supporting
confidence: 90%
“…Several reports have suggested that among unselected patients with severe COPD, the greatest physiological benefit of PAP is achieved in those with higher baseline PaCO 2 levels and in those who receive higher-pressure support and are more compliant [21][22][23]. Importantly, the present study extended these findings to patients who suffered from COPD and concurrent OSA, and demonstrated that CT90% and PCO 2 while awake predict CPAP failure in the OSA-COPD overlap syndrome.…”
Section: Comment [Jm14]supporting
confidence: 70%
“…However, data on its long-term beneficial effects are quite rare. Studies concerning where and how these patients should be followed up in the long term, the criteria for discontinuation and/or continuation of NIV therapy, and how the long-term effects of NIV therapy should be evaluated are limited in number [3,4].…”
Section: Financial Disclosure and Conflicts Of Interestmentioning
confidence: 99%